Compositional and transcriptomic analysis associated with cuticle lipid production on rosette and inflorescence stem leaves in the extremophyte Thellungiella salsuginea. Issue 3 (23rd August 2018) - Tang, Shuai; Chen, Ningmei; Song, Buerbatu; He, Junqing; Zhou, Yijun; Jenks, Matthew A.; Xu, Xiaojing
Abstract : The plant cuticle is a complex structure composed primarily of wax and cutin, but also contains cutan, glycerolipids, phenolics, polysaccharides and proteins. The cuticle plays an important protective role as barrier between plants and their environment. In this paper, 4‐week‐old leaves produced either on the rosette or on the inflorescence stem of the model extremophyte Thellungiella salsuginea were examined using scanning electron microscopy, cuticle permeability assays and chemical composition analysis. Results showed that stem leaves (SL) had more abundant cuticle lipids and lower cuticle permeability than rosette leaves (RL). SL were dominated by alkanes, especially the C29 and C31 homologs, whereas in RL the most abundant wax class was free very long‐chain acids. The major cutin monomers for both leaf types were C18:2 dioic acids and 18‐OH C18:2 acids. We performed Illumina high‐throughput sequencing for SL and RL, and 3577 differentially expressed genes were identified. Sixty‐five genes possibly involved in cuticular lipid biosynthesis, transport, or regulation was selected for further analysis. Many cuticle‐associated genes exhibited differential expression levels that could be associated with compositional differences between these two leaf types. Furthermore, transcription factors and other regulatory proteins previously associated with cuticle production were expressed at higher levels in SL than in RL. The associations between gene expression and characteristics of this extremophile's leaf cuticles sheds new light on cuticle as an adaptive trait in extreme environments, and contributes new information that may guide efforts to modify crop cuticles for improved stress tolerance.